2019
DOI: 10.1136/bmj.l322
|View full text |Cite
|
Sign up to set email alerts
|

Management of perinatal depression with non-drug interventions

Abstract: Perinatal depression is a common disorder that has been associated with serious risks to mother and child. Recently, screening for depression in pregnant and postpartum women has increased, as has the development of new psychotherapy and non-drug treatment modalities. Matching patients to treatments can be challenging, and although research into personalized treatment of major depression in the general population has increased, no published guidelines focus on personalized treatment approaches to perinatal dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 146 publications
0
16
0
1
Order By: Relevance
“…Therefore, family members should focus on the psychological and emotional changes of the mother during "doing the month" period, and have more understanding and companionship for the mother. Besides, we should focus on the factors of maternal dissatisfaction, strengthen postpartum social support treatment, properly extend father's paternity leave to increase father's participation in taking care of baby, and reduce the occurrence of PD [27] .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, family members should focus on the psychological and emotional changes of the mother during "doing the month" period, and have more understanding and companionship for the mother. Besides, we should focus on the factors of maternal dissatisfaction, strengthen postpartum social support treatment, properly extend father's paternity leave to increase father's participation in taking care of baby, and reduce the occurrence of PD [27] .…”
Section: Discussionmentioning
confidence: 99%
“…Zudem sollte immer bedacht werden, dass dabei die betroffenen Mütter von ihrem Alltag separiert werden. Entsprechend muss bei der Rückkehr nach Hause auch die Wiederaufnahme der bisherigen Aufgaben mit eingeübt werden [43].…”
Section: Behandlung Postpartaler Psychischer Störungenunclassified
“…A recent review highlighted the need for more personalised therapies to treat perinatal depression, including interpersonal psychotherapy as a plausible treatment option 17. Women in our patient advisory group consultations reported that CBT is ‘too clinical’ and ‘inflexible’ with practitioners not appearing to consider the circumstances of pregnancy.…”
Section: Introductionmentioning
confidence: 99%